Pathomorphological changes in the large intestine subject to chronic trichuriasis - J. K. Serdioucov; E. V. Mykhailiutenko; O. V. Kruchynenko; S. M. Mykhailiutenko; O. S. Klymenko (Regulatory Mechanisms in Biosystems, 2024)
Trichuris spp. are endoparasites identified in many neotropical rodents. The study was conducted on nutrias (Myocastor coypus Molina, 1782) – semi-aquatic rodents of the family Echimyidae Gray, 1825, held at individual private farms in Poltava Oblast. This study gives us understanding of the species Trichuris myocastoris (Enigk, 1933), diagnosed in the gastrointestinal canal of nutrias. Thus, the objective of the study was to describe pathomorphological changes occurring in the large intestine of nutrias suffering trichuriasis. During the dissection, by macroscopically examining the cavity of large intestine, we detected small white spindle-shaped helminths. Trichuris myocastoris was found to have specific morphological features. Nematodes had a long thread-like front part and thickened, shorter, posterior part. The cuticle was finely striped transversally. In the lumen of large intestine of the nutrias, the average numbers T. myocastoris (n = 15) were found to be 36.7 ± 2.1 in males and 47.7 ± 2.5 in females in summer; and 11.1 ± 1.3 and 16.5 ± 1.2 in winter, respectively. For the histological studies, we chose fragments of the wall of large intestine. Microscopically, in the intestinal lumen, there were recorded transversal or diagonal sections of bodies of the pathogens. The nematodes’ cuticle was stained basophically, and their internal organs eosinophilically. The superficial epithelium of the intestine was ruined in places, and some epitheloicytes were in the intestinal lumen. The intestinal glands were enlarged, filled with mucous content, mostly stained blue-violet, especially in the superficial sections of the glands, i.e. basophilous color. The lamina propria of the mucous membrane, especially between the intestinal glands, was notably infiltrated by lymphoid cells, and individual lymphoid cells were also found in the lumen of intestinal glands and even in the organ’s lumen. Single lymphoid cells also were present in the layer of the mucous membrane. Under large increases, we saw signs of mucous hypersecretion in the goblet cells of the intestinal glands in the form of concentrations of poorly stained mucus granules in cytoplasm. Some goblet cells were ruined, desquamated, and their remains were in the lumens of glands together with mucus. The provided data suggest the relevance of Trichuris invasion as an etiological factor in the emergence of chronic lymphohistiocytic colitis.